The Mechanism of Plasma Destruction of Enalapril and Related Metabolites in Water - Magureanu, Monica; Dobrin, Daniela; Mandache, Nicolae Bogdan; Bradu, Corina; Medvedovici, Andrei; Parvulescu, Vasile I. (Plasma processes and polymers, 2013)
A pulsed dielectric barrier discharge was used for the decomposition of enalapril, its metabolite, enalaprilat, its degradation by‐product, diketopiperazine, as well as their combination, in aqueous solution. The discharge was generated at the interface between gas and the solution which flows as a film on the surface of the inner electrode of the plasma reactor. The degradation mechanism of the studied compounds and the temporal evolution of the reaction intermediates were established from LC–MS analysis. A wide variety of degradation by‐products were formed; at least six new derivatives, not mentioned in literature, were observed. However, most of these by‐products were subsequently degraded to small molecules. The mineralization degree, determined from TOC and COD measurements, was approximately 40%. Non‐thermal plasma in contact with water was tested for the oxidative degradation of enalapril, enalaprilat, diketopiperazine, and their combination. The reaction intermediates were identified and their temporal evolution was followed. Based on the results, degradation pathways of these pharmaceuticals were proposed. The mineralization degree was over 40% and the residual organic matter is composed mainly of small molecules in an advanced oxidation state.